Interpreting of the English Baroque’s Motives in Ukrainian Translations - Demetska, Vladyslava; Kuzenko, Halyna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The article deals with the problem of translation reproduction of English poetry of the Baroque period in the Ukrainian linguistic and cultural tradition through translation studies analysis of four Ukrainian-language translations. Among the age-old challenges of mankind, there are always questions of life and death, which, in particular, are realized through the motif of death, which receives its highest literary and artistic manifestation in the European Baroque period. The research focuses on the problems of reproducing the Baroque consciousness through a poetic image that is reproduced in different dimensions. From this perspective, a comparative translation analysis of the linguistic and semiotic nature of J. Milton’s epitaph “On Shakespeare” is aimed at finding an answer to the question of the translator’s perception of the specifics of the English Baroque, which is reproduced in four translations by I. Franko, Mykhailo Orest, V. Mysyk, and M. Pylynsky. The chosen topic and research material involve several general scientific methods (analysis, synthesis, deduction, induction, observation, and summarization) as well as philological methods (the method of linguistic semiotic analysis in translation semiosis, elements of the biographical method, the comparative method along with linguistic stylistic, descriptive, and comparative translation analysis). The findings suggest that different translation options combine, complement each other, compete with each other, and even negate each other. We believe that the introduction of translation studies of the literary heritage of the pan-European Baroque period with an emphasis on outlining the main factors of the Baroque semiosphere through the prism of translation studies is promising.